Perencanaan dan Kinerja Keuangan Badan Pengelolaan Keuangan Daerah (BPKD) Kabupaten Gowa - Muliati Muliati; Zainal Ruma; Anwar Anwar; Hety Budiyanti; Annisa Paramaswary Aslam (Journal of Management and Social Sciences, 2024)
This research aims to find out the planning of the Gowa Regency Regional Revenue and Expenditure Budget Report (APBD) in 2024 and 2025 using the least squares trend technique and wants to know how well the Gowa Regency Regional Financial Management Agency (BPKD) Financial Performance will be in 2024 and 2025 the future will be based on the regional financial independence ratio, the degree of decentralization ratio and the growth ratio. The type of research used is descriptive quantitative. The data processed is the Regional Revenue and Expenditure Budget Realization Report for 2020 to 2022. The data collection technique used in this research is documentation techniques. The data analysis technique is forecasting using the Trend least square formulation and the regional financial independence ratio, the degree of decentralization ratio and the growth ratio. The results of the research show that the projected regional income and expenditure budget (APBD) report for Gowa Regency in 2024 and 2025 will experience a deficit of IDR. (114,637,699,688.89) and Rp. (166,991,785,688.33). Meanwhile, the financial performance of the Gowa Regency Regional Financial Management Agency (BPKD) in 2024 and 2025 is poor, seen from the results of calculating the regional financial independence ratio, it is classified as very low and in the relationship pattern (Instructive) category, with details: in 2024 it is 19% and in 2025 will be 20%, then the decentralization degree ratio is classified as low, with details: in 2024 it will be 16% and 2025 it will be 17%, and the growth ratio is relatively low, with details: in 2024 it will be 5% and in 2025 it will be 4%.